Catch-and-release behaviour among anglers in Tasik Muda, Kedah - Shaefe, Muhammad Adi Syarqawi (2018)
This study aimed to identify the basic socio-demographic backgrounds, catch-and-release behaviour and fish species preferences among anglers. This study was done at Tasik Muda, Kedah. All anglers that come to fish at Tasik Muda during study period were chosen to answer the survey and face-to-face survey was done. Four variables (attitude, subjective norm, perceived behaviour control and intention) were measured in the questionnaire, along with eight types of fish species that anglers preferred to fish. The data was collected based on a face-to-face on-site survey technique. The results show that most of the respondents were male (90.5%) with a mean age of 36.59 ± 8.80 years old. Most of them are self-employed anglers (45.8%) and a SPM holder (39.5%), with 77.1% are married. The angler’s ‘perceived behaviour control’ was high (3.94 ± 0.78) towards catch-and-release behaviour and it was the main contributing factor that influences the ‘intention’ to perform catch-and-release fishing. Most of the anglers preferred snakehead (Channa striata) (4.54 ± 0.82), Malaysian mahseer (Tor tambroides) (4.65 ± 0.66), copper mahseer (Neolissochilus soroides) (4.51 ± 0.83) and hampala barb (Hampala macrolepidota) (4.47 ± 0.80) as their preferred species while fishing. This study provides some basic data and information about recreational anglers who involved in recreational fishing activity in Tasik Muda, Kedah.